Systemic effects of fluoxetine on the amount of tooth movement, root resorption, and alveolar bone remodeling during orthodontic force application in rat - Mehdi Rafiei; Soosan Sadeghian; Nakisa Torabinia; Valiollah Hajhashemi (Wolters Kluwer Medknow Publications, 2015)
Background: Antidepressant drugs such as fluoxetine are of the most commonly used drugs among the public. These drugs may impact the regulation of bone cell functioning, and thus affect orthodontic tooth movement. The aim of this study was to determine the effect of fluoxetine on tooth movements during orthodontic treatment in rats. Materials and Methods: In this study, 30 male rats were randomly assigned into two groups and injected with fluoxetine 10 mg/kg (experimental group) and normal saline (control group) for a period of 1-month intraperitoneally 5 times/week. Then, the rats were anesthetized and a nickel-titanium closed-coil spring was placed between the left maxillary first molar and left maxillary central incisors of all samples, and then fluoxetine (experimental group) and normal saline (control group) were injected for another 3 weeks by the same method. After measuring tooth movements, rats were sacrificed, and histomorphometric analyses were conducted and the obtained data were statistically analyzed using independent t-test and the significance was set at 0.05. Results: Following the fluoxetine injection, the mean amount of tooth movements in the experimental group was reduced compared to the control group, which was not statistically significant (P = 0.14). There was no significant difference between the two groups regarding bone apposition rate (P = 0.83), external root resorption rate (P = 0.1), and mean number of root resorption lacunae (P = 0.16). Conclusion: Within the limitations of this study, systemic use of fluoxetine may cause insignificant reduction of tooth movement rate in rats; however, this subject needs more evaluations.